miR-145-5p/Nurr1/TNF-α Signaling-Induced Microglia Activation Regulates Neuron Injury of Acute Cerebral Ischemic/Reperfusion in Rats - Xie, Xuemei; Peng, Li; Zhu, Jin; Zhou, Yang; Li, Lingyu; Chen, Yanlin; Yu, Shanshan; Zhao, Yong (Frontiers in Molecular Neuroscience, 2017)
Nurr1 is a member of the nuclear receptor 4 family of orphan nuclear receptors that is decreased in inflammatory responses and leads to neurons death in Parkinson’s disease. Abnormal expression of Nurr1 have been attributed to various signaling pathways, but little is known about microRNAs regulation of Nurr1 in ischemia/ reperfusion injury. To investigate the posttranscriptional regulatory networks of Nurr1, we used a miRNA screening approach and identified miR-145-5p as a putative regulator of Nurr1. By using computer predictions, we identified and confirmed a miRNA recognition element in the 3’ UTR of Nurr1 that was responsible for miR-145-5p-mediated suppression. We next demonstrated that overexpression of Nurr1 inhibited TNF-α expression in microglia by trans-repression and finally attenuated ischemia/reperfusion-induced inflammatory and cytotoxic response of neurons. Results of further in vivo study revealed that anti-miR-145-5p administration brought about increasing expression of Nurr1 and reduction of infarct volume in acute cerebral ischemia. Administration of anti-miR-145-5p promotes neurological outcome of rats post MCAO/R. It might be an effective therapeutic strategy to relieve neurons injury upon ischemia/reperfusion of rats through interrupting the axis signaling of miR-145-5p- Nurr1-TNF-α in acute phase.